Breach of Agreements on Choice of Law - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2010)
Ace v. Moose Ace Insurance Ltd v. Moose Enterprise Pty Ltd is an unexceptional case of the New South Wales Supreme Court that deserves closer attention because it is probably the first common law decision on whether proceedings in a foreign court could constitute breach of a choice of law agreement, thus treading on “territory into which the English courts have not [yet] been invited to go”. The defendant, an Australian company, faced class action litigation in California arising out of allegations that toys it had been distributing—but subsequently recalled—in the United States contained toxic substances. The claimant, an Australian company which had insured the defendant against personal injury claims, initially defended the actions on behalf of the defendant. The claimant afterwards informed the defendant that it would stop doing so on the ground that the claims pursued in the class actions did not fall within the cover of the policy. The defendant then started proceedings in California seeking a declaration that the claimant was obliged under the law of California to defend the actions. The claimant responded by taking out proceedings in New South Wales for an anti-suit injunction to prevent the defendant from continuing the Californian proceedings. The insurance contract was made in Australia, and the critical clause was: “Should any dispute arise concerning this policy, the dispute will be determined in accordance with the law of Australia and the States and Territories thereof. In relation to any such dispute the parties agree to submit to the jurisdiction of any competent court in a State or Territory of Australia”. Brereton J granted the anti-suit injunction on the familiar ground that the Californian action was in breach of the jurisdiction agreement in the parties’ contract, and that in any event the foreign conduct was vexatious and oppressive. 4 He found that, although the parties had not expressly used the word “exclusive” in the jurisdiction clause, as a matter of construction the parties had intended the Australian court to have exclusive jurisdiction, and the defendant was therefore under a contractual obligation not to continue the proceedings in California. The more interesting aspect of the judgment lies in the treatment of the contention of counsel for the claimant, based primarily on the suggestions of Professor Adrian Briggs.